Cancer risk stratification: the role of polygenic risk scores - Pharoah, Paul (Henry Stewart Talks, 2021)
The role of inherited genetic variation in cancer risk with a focus on breast cancer, What is a risk single nucleotide polymorphism (SNP)?, How multiple risk SNPs combine to affect risk, The multiplicative model of polygenic risk, Implications of polygenic risk scores for breast cancer risk prevention in the population